2016
DOI: 10.1007/s10571-016-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-373 Inhibits Glioma Cell U251 Migration and Invasion by Down-Regulating CD44 and TGFBR2

Abstract: Glioblastoma multiforme (GBM) is the most malignant glioma, unveiling the underlying mechanisms of its aggressiveness could promote the discovery of potential targets for effective treatment. MicroRNAs (miRNAs) are important participants in both development and disease, its involvement in cancers has long been recognized. In this study, we investigated the role of miRNA-373 (miR-373) in GBM cell line U251, demonstrated that although miR-373 does not affect cell growth of U251, it inhibits migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…As TGFb signaling is known to induce transcriptions factors ZEB1, ZEB2, and SNAI2, miR-520f might downregulate these transcription factors through targeting TGFBR2 (36,37). Furthermore, knockdown of TGFBR2 has been shown to inhibit tumor cell invasion (38,39). This is in line with our results showing that siRNA mediated knockdown of TGFBR2 inhibits tumor cell invasion.…”
Section: Discussionsupporting
confidence: 89%
“…As TGFb signaling is known to induce transcriptions factors ZEB1, ZEB2, and SNAI2, miR-520f might downregulate these transcription factors through targeting TGFBR2 (36,37). Furthermore, knockdown of TGFBR2 has been shown to inhibit tumor cell invasion (38,39). This is in line with our results showing that siRNA mediated knockdown of TGFBR2 inhibits tumor cell invasion.…”
Section: Discussionsupporting
confidence: 89%
“…Notably, the TGF-β-SMAD pathway confers poor prognosis to glioma patients and promotes cell proliferation (24). TGFBRII is a critical component of the TGF-β signaling pathway and TGFBRII silencing blocked the effects of TGF-β1 in glioma cells (25). In the present study, we found that miR-520c negatively regulated the abundance of TGFBRII in glioma cells.…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with this evidence, the results in this study showed that the ectopic expression of miR-373 reduced VM formation in U87 and U251 glioma cells. Wei et al [54] showed that miR-373 inhibits U251 glioma cell migration and invasion but does not affect proliferation in U251 cells. However, our results showed that miR-373 suppressed malignant behaviors inU87 and U251 cells, including cell viability.…”
Section: Discussionmentioning
confidence: 99%